2015
DOI: 10.1373/clinchem.2014.226571
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal Instability in Cell-Free DNA Is a Serum Biomarker for Prostate Cancer

Abstract: BACKGROUND Genomic instability resulting in copy number variation is a hallmark of malignant transformation and may be identified through massive parallel sequencing. Tumor-specific cell free DNA (cfDNA) present in serum and plasma provides a real-time, easily accessible surrogate. METHODS DNA was extracted from serum of 204 patients with prostate cancer (Gleason score 2–10), 207 male controls, and patients with benign hyperp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 38 publications
0
28
0
Order By: Relevance
“…Recent studies have explored the utility of copy number variations presenting in cell-free DNA (cfDNA) fragments in serum/ plasma as a potential clinically useful biomarker to detect prostate cancer, giving a diagnostic accuracy of 83% [13]. With the whole-genome analyses of cfDNA, Leary, et al identified chromosomal alterations present in all plasma of advanced-stage cancer patients [12].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have explored the utility of copy number variations presenting in cell-free DNA (cfDNA) fragments in serum/ plasma as a potential clinically useful biomarker to detect prostate cancer, giving a diagnostic accuracy of 83% [13]. With the whole-genome analyses of cfDNA, Leary, et al identified chromosomal alterations present in all plasma of advanced-stage cancer patients [12].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, additional predictive factors of prognosis are needed to better evaluate therapy outcomes and help develop individualized treatment plans. Several methods have been used to identify new biomarkers for CRC, including translational approaches investigating perturbations in gene expression or genomic instability, which can be identified using animal models of CRC [21], and high-throughput technologies such as massive parallel sequencing [22]. Bioinformatics methods combined with public cancer databases also have been widely used to find potential biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…In this view, the analysis of the genomic instability resulting in copy number aberrations through massive parallel sequencing, as already demonstrated for prostate cancer [11] or the detection of tumorderived circulating cell-free DNA in plasma samples [12] could represent new possibilities for the detection and monitoring of CRC to investigate in the AOM/DSS murine model.…”
Section: Introductionmentioning
confidence: 99%